PELAKSANAAN ALUR SIRKULASI LINEN DALAM SISTEM KERJA HOUSEKEEPING DI SECTION LAUNDRY HOTEL PANGERAN PEKANBARU - Olyvia Laras Santri; Andi M. Rifiyan Arief (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
A system management is a process associated with the implementation of indicators ofmanagement or management functions that play an important and effective role in supportingthe achievement of goals. the management of the room linen at Hotel Pangeran Pekanbaruincludes the control of all the fabrics contained in a hotel room which includes bath towel, handtowel, face towel, sheet, bad pad, curtain and bath mat. Linen Circulation Flow Steps includeLinen Inventory, Par Stock, Repair, Linen Control, Linen Exchange and Wash Standart. Thedata were analyzed descriptively. Methods of data collection using, interview, observation anddocumentation.Linen control of the linen at the hotel Pekanbaru can be said good in checking thecondition of linen is also good. about the frequency of redundant linen exchange is categorizedvery well, because linen is exchanged every time it is used for filled rooms. The linen exchangeindicator and linen leaching standard are categorized quite well.Keywords: Linen Inventory, Part stock, Repair, Linen control, linen exchange, StandartWashing.